1, 3‐butadiene polymerization using Co/Nd‐based Ziegler/Natta catalyst: Microstructures and properties of butadiene rubber. Issue 1 (3rd February 2014) - Chatarsa, Chansuree; Prasassarakich, Pattarapan; Rempel, Garry L.; Hinchiranan, Napida
<x xml:space="preserve">Abstract</x> Among Ziegler‐Natta catalysts used for 1, 3‐butadiene (1, 3‐BD) polymerization, the advantage of a neodymium (Nd)‐based catalyst is that it provides butadiene rubber (BR) with a high content of cis−1, 4 configuration and a low amount of vinyl−1, 2 units. Whereas, a cobalt (Co)‐based catalyst can produce BR with a low content of trans−1, 4 configuration. Thus, this research was aimed to prepare BR containing a high content of cis−1, 4 configuration with low amounts of both trans−1, 4 and vinyl−1, 2 units using a combination of Nd‐ and Co‐based Ziegler/Natta catalysts with triethyl aluminum (TEAL) and diethyl aluminum chloride (DEAC) acting as a co‐catalyst and a chlorinating agent, respectively. The effects of the molar Co/Nd ratio, TEAL concentration, DEAC loading, 1, 3‐BD content, solvent type, and reaction temperature on % conversion, microstructures, molecular weight, and molecular weight distribution of the obtained BR (Co/Nd‐BR) were evaluated. The Co/Nd‐BR having >97% of cis−1, 4 configuration, <2% of trans−1, 4 structure, and <1% of vinyl−1, 2 unit with >80% conversion was achieved when 3.01 M of 1, 3‐BD concentration was treated in a toluene/cyclohexane mixture (7/3 [w/w]). The Co/Nd‐BR exhibited no gel formation with high mechanical performance, which was equivalent to commercial BR produced from a Nd‐based catalyst system. POLYM. ENG. SCI., 55:14–21, 2015. © 2014 Society of Plastics Engineers